2002
DOI: 10.1097/00002060-200201000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Postural Sway and Active Balance Performance in Highly Active Lower-Limb Amputees

Abstract: Amputees had poorer static and dynamic balance than able-bodied controls. Amputees had a greater problem controlling dynamic balance in the anteroposterior direction than the mediolateral direction. Findings highlight the importance of the ankle in maintaining balance in situations that involve body movements in the sagittal plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 18 publications
10
107
1
5
Order By: Relevance
“…Experienced transtibial prosthesis users are able to complete activities of daily living (ADLs) effectively, and the successful completion of these tasks is an integral part of regaining an independent lifestyle [1][2][3][4][5]. However, psychological issues, such as how an amputee feels about his or her amputation and prostheses, are also important factors.…”
Section: Introductionmentioning
confidence: 99%
“…Experienced transtibial prosthesis users are able to complete activities of daily living (ADLs) effectively, and the successful completion of these tasks is an integral part of regaining an independent lifestyle [1][2][3][4][5]. However, psychological issues, such as how an amputee feels about his or her amputation and prostheses, are also important factors.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased costs, rehabilitation programmes have problems in ensuring sufficient therapy in relation to prostheses [1]. What's more, the trend of expanding outpatient rehabilitation increases the unavailability of these services to amputees.…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 99%
“…Pathological function of one or more of these physiological systems can be a contributing factor in falling [4][5]. Individuals with lower-limb amputations have reduced measures of postural stability [6][7][8][9] as determined by increased excursion of the center of pressure (CoP) and sway amplitude [9] in the mediolateral [6][7] and anteroposterior directions. Moreover, they identify postural stability as an important criterion for functioning with a prosthesis [10], and they have been shown to fall more than age-matched nondisabled individuals [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Most of our current understanding of postural stability of individuals with an amputation has been provided by various measures of movement of the CoP on a stationary [6][7][8][9][13][14] or unstable surface [6,[15][16]. Several studies have demonstrated increased excursion of the CoP in the anteroposterior direction [13,16] or both the anteroposterior and mediolateral directions [6][7]9,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation